Supression of mechanical oscillations in a nonlinear systems with restriction - Zaksienė, Genovaitė (Lietuvos matematikos rinkinys, 2023)
The application of the dynamical dampers in the mechanical systems, when the sources of stimulation are impossible to abolish, is one of the ways to fight against the harmful vibrations. The linear dynamical damper of nonlinear systems can compensate the force of stimulation in wide diapason of frequency. The parameters of dynamical system where dynamical damper exists more effectively are determined.